Efficacy of Mindfulness Strategies in The Reduction of Domestic Violence Among Nigerian Couples - Olukorede Patricia Adisa; Janet Atere Blessing; Ajibade Bayo Lawal (Indonesian Journal of Nursing and Health Care, 2026)
Background: Domestic violence (DV) is a global public health problem of human rights concern, affecting any gender; yet considered a private family matter, increasing the chances of temporary or permanent disabilities, depression, and suicide. Mindfulness-based strategies holds promise for mitigating these consequences by enhancing self-compassion, self-esteem and coping levels in women who have experienced violence. The study aimed to assess the efficacy of mindfulness strategies in the reduction of DV among couples.Objective: The study aimed to assess the efficacy of mindfulness strategies in the reduction of DV among couples.Methods: The study design was a one-group pretest-posttest design conducted on forty-eight respondents over a period of 12 weeks. It utilized a non-probability sampling method with the aid of structure-interviewer administered questionnaire before and after the intervention. Data obtained were analyzed using SPSS version 25.Results: The overall level of knowledge of domestic violence was good. Factors influencing domestic violence include substance abuse (100%), job loss (83.3%), poverty and stress (95.8%), gender preferences and inequality (87.5%) and mental illness (85.4%). There was a statistically significant difference between the score of mindfulness before intervention and after intervention (p value of 0.001) and 68.8% of the respondents were improved with the mindfulness strategies.Conclusion: This study provides preliminary evidence that mindfulness strategies may reduce DV among low-income Nigerian couples. It is recommendation that this technique be employed in various settings including religious centers, counselling units and couple’s forums to reduce the incidence of domestic violence related issues among couples.